Reactions, Challenges, and Coping Resources of College Teachers Who Have Encountered Students With Diagnosed Psychological Disorders - Deleña, Mary Irene Clare O. (Animo Repository, 2018)
This research identified the experiences of college teachers who have encountered students with diagnosed psychological disorders. Respondents are 14 college teachers from various colleges of a private university. All experiences shared through one-on-one interview are with students of the same university. This paper presents their reactions, challenges, coping resources, and recommendations. After conducting a qualitative analysis, it was realized that college teachers share common reactions, challenges, and coping resources in the situations that they experienced dealing with these students. Various means of reaching out were generally given by college teachers depending on their individual strategies. Behavioral reactions of giving considerations, referring to a professional or an authority, and treating the student normally, as well as the affective reaction of being concerned, were expressed. Challenges relating to the lack of professional skills, balancing considerations given and being fair to other students, and knowing the limits of one’s ability to help were typical among participants. Lastly, coping resources relating to seeking knowledge on mental health, seeking assistance from professionals, sharing experiences with other faculty members, and praying were found to be variant. With all these reactions, a typical recommendation for fellow faculty members who might be having similar experiences was to be kind and sensitive to these students. In addition, a typical recommendation for administrators was to provide training on helping skills and early detection of symptoms of psychological disorders.